Advances in structural and multidisciplinary optimization : proceedings of the 12th World Congress of Structural and Multidisciplinary Optimization (WCSMO12) /: proceedings of the 12th World Congress of Structural and Multidisciplinary Optimization (WCSMO12). ([2018]) - Unknown
No abstract available